Information Systems Foundations: Theory Building in Information Systems - N. Hart, Dennis (ANU Press, 2012)
This volume presents the papers from the fifth biennial Information Systems Foundations Workshop, held at The Australian National University in Canberra from 30 September to 1 October 2010. The focus of the workshop was, as for the others in the series, the foundations of information systems as an academic discipline. The emphasis in the 2010 workshop was on theory building in information systems, which is a non-trivial and difficult issue because the field deals with such a wide range of phenomena, from the highly technological in nature to the distinctly human and organisational in focus. The theory building problem stems from the fact that the sciences that underlie and deal with technologically-oriented fields generally result in theories that fit within the 'covering law' model-that is, are assumed and believed to have universal applicability and explanatory and predictive power-whereas, by contrast, theories in the human sciences are generally much more conditional, contextual, tentative and open to exceptions. Successfully marrying the two is, not surprisingly, a challenge that the chapters in this volume explore.